Implementation of the Baby-Friendly Hospital Initiative in Mexico: a systematic literature review using the RE-AIM framework - Bueno, Angela K.; Vilar-Compte, Mireya; Cruz-Villalba, Valeria; Rovelo-Velázquez, Natalia; Rhodes, Elizabeth C.; Pérez-Escamilla, Rafael (Frontiers in Public Health, 2023)
The Baby-Friendly Hospital Initiative (BFHI) is a global strategy to encourage health facilities to promote, support, and protect breastfeeding by implementing a package of policies and practices known as the Ten Steps to Successful Breastfeeding. Prior studies have found that implementing the Ten Steps has a positive impact on breastfeeding outcomes. Yet, little is known about the implementation of the Ten Steps in Mexico. The objective of this study was to conduct a systematic review to evaluate the reach, efficacy/effectiveness, adoption, implementation, and maintenance of the Ten Steps in Mexico, using the RE-AIM framework. The systematic literature review included studies published in English or Spanish without date restrictions. Two of the authors coded each of the articles through a harmonized data extraction tool, and group meetings were used to discuss any discrepancies. The reviewed data were managed in the Rayyan platform. The risk of study bias was assessed through the Johanna Briggs Institute critical appraisal checklists. Of the 1,123 articles initially identified, 6 met the review inclusion criteria. None of the articles evaluated the reach and maintenance of the Ten Steps. The articles identified major gaps in the implementation of the Ten Steps. Most of the articles had important limitations in terms of their quality. In Mexico, it is necessary to rethink the BFHI and employ multiple strategies to improve implementation of the Ten Steps, including developing transparent BFHI monitoring mechanisms that produce data on implementation and that are publicly available, as well as investing in implementation research and evaluation to generate strong evidence to support the adoption and efficient maintenance of the Ten Steps in health facilities in Mexico. When properly implemented, BFHI becomes central to promote, protect, and support breastfeeding. Therefore, it is essential for Mexico to position BFHI as a top priority of the country's public policy agenda. Systematic Review Registration identifier: CRD42021248118.